Weak bases, an efficient accelerator for the RAFT of isoprene. Issue 8 (2nd August 2020) - Xiang, Yixin; Zhao, Haibing; Shen, Xianrong; Gao, Jiangang; Asiri, Abdullah M.; Marwani, Hadi M.
Abstract: The use of weak bases as accelerators for reversible addition-fragmentation chain transfer radical polymerization (RAFT) of isoprene is demonstrated. Adding weak bases to RAFT polymerization, the conversion of isoprene could be greatly improved and reach about 50%. The effects of weak base on the polymerization were investigated. The living and controlled character of the RAFT polymerization of isoprene was confirmed by the linear increase in molecular weight with monomer conversion, the narrow molecular weight distribution and synthesis of polyisoprene- block -polystyrene (PIP- b -PS) block copolymer. The results of 1 HNMR spectroscopy show that the structure of polyisoprene (PIP) with weak bases as accelerators was the same to the structure of PIP without any accelerator. The data presented here prove that weak bases are an efficient accelerator to inhibit Diels-Alder reaction of isoprene in the RAFT polymerization. GRAPHICAL ABSTRACT: Weak bases were used as accelerators for reversible addition-fragmentation chain transfer radical polymerization (RAFT) of isoprene. Diels-Alder reaction of isoprene in RAFT polymerization was inhibited by adding a small amount of weak alkaline monomer (4-methyl-5-vinylthiazole and 4-vinylpyridine), and the conversion of isoprene was greatly increased. Some weak bases including pyridine, bipyridine, oxazole, pyrazole, benzothiazole and quinoline, were used to inhibit Diels-Alder reaction of isoprene. The living and controlled character of the RAFT polymerization of isoprene was confirmed by the linear increase in molecular weight with monomer conversion, the narrow molecular weight distribution and synthesis of polyisoprene- block -polystyrene (PIP- b -PS) block copolymer.